Mastery of Sumber Urip-1 farmer group in Malang Regency in the production and application of organic auxins and gibberellins - Budiyanto, Moch. Agus Krisno; Rahardjanto, Abdulkadir; Waluyo, Lud (Universitas Muhammadiyah Malang, 2020)
Organic agriculture was a manifestation of sustainable agriculture as stipulated in SDG 2. Therefore, farmer assistance activities were needed to implement organic agricultural applications, namely the manufacture and use of organic auxins and gibberellins. This communityservice aimed to provide assistance in the manufacture and use of organic auxins and gibberellins. The method in implementing this activity was direct assistance and practice to solve problems. The activity was held for three months, in Wonorejo Village, Poncokusumo District, Malang Regency, East Java Province, with a partner named Sumber Urip-1 Farmer Group. The indicator for the success of community service activities was that> 75% of the members (out of a total of 20 people) can practice making organic auxins and gibberellins. To improve mentoring performance, there was team synergy in the form of division of labor, cooperation patterns, and collaboration patterns. Evaluation and monitoring of activities was carried out by holding morning meetings every Friday. Through a series of activities, partners have mastered the methods of (1) manufacturing and (2) using organic auxins and gibberellins. Products were branded with the brands